SPIRITUAL AND AESTHETIC DIMENSIONS OF TARTIL AND TILAWAH: A STUDY OF THEMATIC INTERPRETATION - Miftahul Rizkiah Haling; Syam, Nurfadhilah; Mukmin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to examine the concepts of tartil and tilawah in the Qur'an and to identify the values contained within them through a thematic interpretation (maudhu’i) approach. The phenomenon of Qur'an recitation in society still tends to focus more on technical aspects, such as fluency and the beauty of the recitation, while the aspects of understanding and internalizing Qur'anic values have not become a primary concern. The method used is qualitative research with a literature study approach, with the main data consisting of Qur'anic verses related to tartil and tilawah, such as QS. al-Muzzammil [73]: 4, QS. al-Furqān [25]: 32, QS. al-Baqarah [2]: 121 and 129, QS. Fāṭir [35]: 29, QS. Āli ‘Imrān [3]: 113, QS. Yūnus [10]: 61, and QS. an Naml [27]: 92, which are analyzed through Tafsir Ibnu Katsīr, Tafsir al-Mishbah, and Tafsir al Jalālain. The results of the study indicate that tartil means reading the Qur'an slowly, orderly, and in accordance with the rules of tajwid, while tilawah encompasses reading accompanied by understanding, contemplation (tadabbur), and the practice of Qur'anic values. The values contained within it include precision, devotion, sincerity, faith, and moral responsibility. This research emphasizes that tartil and tilawah serve not only as reading techniques but also as means of fostering Qur'anic character that touches upon spiritual, intellectual, and social dimensions.